Base-resolution analysis of 5-hydroxymethylcytidine by selective oxidation and reverse transcription arrest. Issue 29 (9th July 2021) - Koyama, Kenta; Hayashi, Gosuke; Ueda, Hiroki; Ota, Satoshi; Nagae, Genta; Aburatani, Hiroyuki; Okamoto, Akimitsu
Abstract : A base-resolution analysis of RNA hm5 C "WT-Seq" has been developed using the peroxotungstate-mediated oxidation and subsequent truncated cDNA production. Abstract : While 5-hydroxymethylcytidine in RNA ( hm5 C) is associated with cellular development and differentiation, its distribution and biological function remain largely unexplored because suitable detection methods are lacking. Here, we report a base-resolution sequencing method for hm5 C in RNA by applying peroxotungstate-mediated chemical conversion of hm5 C to trihydroxylated thymine ( th T). Reverse transcription by SuperScript III terminated at the th T site, probably because of its unnatural nucleobase structure producing truncated cDNA. Consequently, base-resolution analysis of the hm5 C sites in RNA was achieved with both Sanger sequencing and Illumina sequencing analysis by comparing sequencing data before and after peroxotungstate treatment.